2021
DOI: 10.3389/fevo.2021.700962
|View full text |Cite
|
Sign up to set email alerts
|

Rules of Plant Species Ranges: Applications for Conservation Strategies

Abstract: Earth is changing rapidly and so are many plant species’ ranges. Here, we synthesize eco-evolutionary patterns found in plant range studies and how knowledge of species ranges can inform our understanding of species conservation in the face of global change. We discuss whether general biogeographic “rules” are reliable and how they can be used to develop adaptive conservation strategies of native plant species across their ranges. Rules considered include (1) factors that set species range limits and promote r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 254 publications
(385 reference statements)
0
22
0
Order By: Relevance
“…Values of genetic diversity across the studied Northern Iberian region Historical and recent processes shape the genetic variation and population differentiation present in natural populations (Maroso et al 2021). Maintenance of genetic diversity can be a challenge for populations located at the limits of the species range because isolation and extinction/colonization events are frequent (Cires et al 2011), but these populations can retain singular variants of high interest for conservation (Travis and Dytham 2004;Shay et al 2021) and their human use should be rational and controlled. Arnica montana populations in the Iberian Peninsula represent the southern edge of the natural distribution of the species (Falniowski et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Values of genetic diversity across the studied Northern Iberian region Historical and recent processes shape the genetic variation and population differentiation present in natural populations (Maroso et al 2021). Maintenance of genetic diversity can be a challenge for populations located at the limits of the species range because isolation and extinction/colonization events are frequent (Cires et al 2011), but these populations can retain singular variants of high interest for conservation (Travis and Dytham 2004;Shay et al 2021) and their human use should be rational and controlled. Arnica montana populations in the Iberian Peninsula represent the southern edge of the natural distribution of the species (Falniowski et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor affecting plant population genetic structure is spatial distribution [ 1 , 15 ]. Plant species can occur in uniform, clumped, or random distributions, or, for instance, along an elevation gradient; and the ranges of species may vary in size from widespread to very narrow and endemic.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that species which have narrow temperature or precipitation tolerances are the most likely to be affected by climate change (Slatyer et al, 2013). However, empirical evidence is still limited (Shay et al, 2021) and for many species we do not know the factors that limit their distributions, whether leading edge expansions are sustainable, or how these species respond to climate change. Gaining a better understanding of the physical factors underlying the distribution of organisms is crucial to predict how species will respond to climate change (Hagsater et al, 1996;Tsiftsis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A recent modelling study has indeed shown that predicted changes in climatic conditions increased habitat suitability available to three Orchis species by 2050 at the northern edge of their distribution . However, given that these species showed very similar distribution areas and often co-occur, such a generalisation may not be appropriate and it remains unclear how differences in range size or environmental niche breadth predict vulnerability under global change (Shay et al, 2021).…”
Section: Introductionmentioning
confidence: 99%